Legal Implications Of Ai-Assisted Medical Waste Management In Healthcare Facilities - Sebastian, Rommy; Sara, Rineke (Jurnal Locus Penelitian dan Pengabdian, 2024)
Medical waste management in healthcare facilities is critical to protecting public health and the environment. Improper handling of medical waste can lead to environmental pollution and pose serious health risks. In Indonesia, Permenkes No. 2 of 2023 provides a regulatory framework for managing medical waste, but its implementation needs to be improved, especially in remote healthcare facilities with limited infrastructure and resources. Technological advances, especially artificial intelligence (AI), offer potential solutions to optimize medical waste management through real-time tracking, sorting, and monitoring. This study aims to evaluate the role of AI in supporting the implementation of Permenkes No. 2 of 2023 in several health facilities and identify barriers to AI adoption. Using a normative legal approach combined with case studies from health facilities in Indonesia, this study highlights the effectiveness of AI implementation in medical waste management. The results show that AI has the potential to improve compliance with medical waste management standards, optimize waste processing, and strengthen supervision through real-time data collection. However, AI adoption faces high costs, a lack of infrastructure, and limited technical expertise, especially in remote areas. The implications of this study emphasize the need for investment in technological infrastructure, health workforce training, and supportive policies to address barriers to AI adoption. This would maximize the potential of this technology in more effective medical waste management for public health and a safer environment.